ANALYSIS OF THE PARAMETERS AND ABUNDANCE OF N-CAPTURE ELEMENTS FOR FOUR STARS WITH DIFFERENT METALLICITY - Basak, N. Yu.; Mishenina, T. V. (Одеські астрономічні публікації, 2013)
Based on the spectra obtained with echelle spectrograph SOPHIE (1.93 mtelescope, OHP,France) and the selection of lines (Basak & Mishenina, 2012). we have redefined the parameters and have determined the abundances of the elements produced in the process of neutron captures for stars HD 6582, HD19445, HD 84937, HD170153. Obtained abundance of Y, Zr, La, Ce, P, Nd, Sm, and Gd, shows the solar scaled abundance distribution